COMBINATION ANTIHYPERTENSIVE THERAPY: WHEN THE WHOLE IS GREATER THAN THE SUM OF ITS PARTS - E. O. Taratukhin; N. V. Teplova (Кардиоваскулярная терапия и профилактика)
The paper discusses the importance of high treatment compliance in the case of long-term or life-long therapy. This problem can be resolved by the use of combination pharmacological treatment, such as the combination of a calcium channel blocker and an ACE inhibitor. Apart from the higher treatment compliance, this combination provides additional metabolic benefits, due to the beneficial metabolic effects of its components.